Effect of COVID-19 on air pollution related illnesses in India. (June 2022) - Uday, Utkarsha; Bethineedi, Lakshmi Deepak; Hasanain, Muhammad; Ghazi, Behram Khan; Nadeem, Arsalan; Patel, Prashastee; Khalid, Zaira
Abstract: Ambient air pollution level not only causes respiratory diseases but also cardiovascular diseases, besides, increased visits to the emergency department for asthma, chronic obstructive pulmonary disease (COPD), bronchitis, allergic rhinitis, attention deficit hyperactivity disorder (ADHD) in children and premature deaths in infants. The occurrence of Coronavirus-19 (COVID-19) pandemic is both, a boon and bane. Despite the deplorable situation aroused by the pandemic, strict lockdown measures implemented to curb the drastic spread of the disease, also culminated into astonishing outcomes that were not prioritized. This article illustrates the effects of the ongoing pandemic on air pollution and provides recommendations aimed at limiting it.